Anishinaabe Treaty-Making in the 18th-and-19th-Century Northern Great Lakes: From Shared Meanings to Epistemological Chasms - Corbiere, Alan Theodore Ojiig (2020)
This dissertation looks at the evolution of Anishinaabe treaty-making process via the diplomatic language and implements used (wampum, calumet pipes, medals, clothing, texts, and paper). Anishinaabe people include the Ojibwe, Odaawaa, Potawatomi, Mississauga, Algonquin, Nipissing and Saulteaux. Treaties amongst Indigenous people are explored as foundational precursors to treaties with colonial entities. Continuity in procedures, forms, discourse, metaphors and implements, are revealed. The Anishinaabe treaty process is an oral-based practice that combines material elements which are used as mnemonic devices while colonial treaty partners emphasize text-based procedures and materials, resulting in a tension between literacy and orality. The analysis adopts an Anishinaabe-centric perspective utilizing council proceedings, treaty councils, and petitions, privileging Anishinaabe voices through time. The analysis is also informed by explicating sources such as wampum belts and strings, medals, calumets, and Anishinaabemowin (Ojibwe language) to produce a more nuanced interpretation of Anishinaabe governance structures and their role in treaty procedures.